Efficacy of Epinephrine in Fluid Refractory Septic Shock in Children:A Prospective Observational Study - Thapa, Prakash; Basnet, Sudha (Medical Journal of Armed Police Force Nepal, 2026)
Introduction: Septic shock is a leading cause of mortality and morbidity among children globally. Although dopamine has traditionally been used, emerging evidence suggests epinephrine may be more effective. This study was conducted to identify the proportion of children responding to epinephrine and to document associated survival outcomes and side effects in a resource-limited tertiary setting. Methods: This prospective observational study was conducted over 14 months at a tertiary care university hospital. Ethical approval was obtained from the hospital’s institutional ethics committee (Reference number: 184/075/076). We enrolled 31 children aged 1 month to 16 years with fluid-refractory septic shock. Participants received epinephrine infusions at incremental doses starting at 0.1 μg/kg/min and escalating by 0.1 μg/kg/min every 10 minutes to a maximum of 0.3 μg/kg/min until shock resolution. Outcomes included the proportion of shock resolution, survival, and duration of hospital stay. Data were entered in Epidemiologic Information and Microsoft Excel. Results: Shock resolved in 24 (77.40%) patients with epinephrine alone, while 7 (22.60%) patients achieved resolution within the first hour, and 7 (22.60%) required additional vasoactive agents, primarily noradrenaline. Side effects included feeding intolerance in 3 (9.60%) and hyperglycemia in 2 (6.40%) children. There were 7 (22.60%) deaths, and 24 (77.40%) children survived to discharge. Conclusions: Epinephrine could be considered an effective agent for the reversal of fluid-refractory septic shock in children. It appeared to offer survival benefits with minimal life-threatening side effects in this cohort.